Re-imagining Metro Manila: Potential Impacts of Mass Transit for a Megalopolis - Aloc, Dominic S.; F. Regidor, Jose Regin (Institut Teknologi Sepuluh Nopember, 2017)
Metro Manila is a metropolis comprised of 15 cities and 1 municipality with a population of over 13 million people. It is already considered as a megalopolis together with adjoining provinces to the north, east and south. Despite it being highly urbanized, the city is dependent of road-based transport, with about 80% of commuters taking public transportation but with 70% of road space taken up by cars. Metro Manila currently has only 4 railways lines – Line 1 along Taft Avenue, Rizal Avenue and EDSA, Line 2 along Aurora Boulevard and Marcos Highway, Line 3 along EDSA, and the commuter line of the old Philippine National Railways. If plans formulated since the 1970s were realized, then commuting would have been very different in Metro Manila, where majority of commuters could have been using rail-based transport. This study examines the counterfactual scenarios of mass transit development in the context of co-benefits for Metro Manila over the past four decades, focusing on rail transport. The outcomes of simulated scenarios are used as inputs towards the quantification of transport co-benefits. These co-benefits include improved air quality, more efficient fuel consumption, safer roads, and reduced travel time. The evaluation procedure was based from the Transport Co-benefits Guidelines developed by the Institute of Global Environmental Strategies. The assessment of transport and traffic conditions as related to rail-based mass transit development showed a very significant potential for alleviating transport and traffic congestion in Metro Manila, thereby improving the quality of life for people.